Screening of Antiradical Activity From Some Central Sulawesi Mangroves - Didit Kustantio Dewanto; Wendy Alexander Tanod; Finarti Finarti; Renol Renol (Pharmaciana, 2018)
Antiradicals are substances with important functions for human health. Mangrove leaves are one of potential sources of natural antiradical. The objective of this research was to identify the type and fraction of mangrove leaves extract with the highest antiradical activity. The research procedure included sampling and extraction of mangrove leaves, assay of antiradical activity (DPPH), phytochemical assay and determination of IC50 for the fraction with the highest inhibition percentage. Mangrove leave samples (Rhizophora sp., Avicennia sp. and Sonneratia sp.) used in this study were collected from the Palu Bay coastal. Results showed the highest yield of extracts was from Rhizophora sp., followed by Avicennia sp. and Sonneratia sp. Inhibition percentage was higher from dried compared to fresh mangrove leaves. Additionally, the inhibition percentages of the ethanol fraction was higher than that of the ethyl acetate and n-hexane fractions, while Sonneratia sp. gave a higher inhibition percentage than Avicennia sp. and Rhizophora sp. The ethanol fraction IC50 was determined for Sonneratia sp. (46.05 ± 0.18 µg/mL), Avicennia sp. (88.41 ± 0.29 µg/mL) and Rhizophora sp. (103.95 ± 0.38 µg/mL). Phytochemical assays showed that the three ethanol fractions contained flavonoids, phenols (tannins) and steroids compounds. From the research, it can be concluded that the three leaves of mangrove potential as antiradicals.